Autologous Abdominal Dermal Grafts for Immediate Prosthetic Breast Reconstruction - A Preliminary Study - Ana Beatriz Morais Silva (2021)
BACKGROUND: Breast reconstruction techniques are in constant growth. Acellular dermal matrices (ADM) have been extensively used for years and have demonstrated several advantages. However, ADM add significant cost to the procedure and were associated with complications such as seroma, infection and mastectomy flap necrosis. Dermal autografts may represent a safe alternative. The aim of our study is to perform a literature review and evaluate the efficacy and safety of autologous abdominal dermal grafts for prosthetic immediate breast reconstruction. METHODS: This was a retrospective study that included all patients who underwent immediate breast reconstruction with autologous abdominal dermal grafts after skin-sparing mastectomy in a 4-year period. Information was extracted from patient's hospital records. Complications were recorded and compared with published data. RESULTS: Six patients for a total of six breasts were included in this study. The reconstruction with autoderm was successful in four patients (66.7%) and failed in two patients (33.3%). The latter represented high risk patients for immediate breast reconstruction (active smoker and overweight) with mastectomy flap necrosis and infected seroma from sentinel biopsy zone. No donor-site complications were reported. It was possible to harvest a transverse rectus abdominis musculocutaneous (TRAM) flap in one of the failed cases. CONCLUSIONS: The utilization of abdominal dermal grafts for immediate prosthetic breast reconstruction may be a good alternative to acellular dermal matrices, particularly in normal weight or very thin patients who are not candidates for autologous reconstruction. Further studies are needed to validate this surgical option.